1977
DOI: 10.1002/jcp.1040930109
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A‐binding by cells of the early chick embryo

Abstract: The surfaces of cells from the early embryo of the chick were examined using electron microscope techniques for the visualization of concanavalin A-binding sites. Horseradish peroxidase and Ferritin labelled concanavalin A were used to determine the distribution of the binding sites. All surfaces of the epiblast and hypoblast layers which were accessible to concanavalin A showed the presence of binding sites in stage 1 embryos. The ventral surface of the epiblast showed a high lectin affinity which may reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It has been shown that Con A-binding sites change quantitatively during development in the ectoderm of amphibian neurulae (O'Dell etal. 1974), in chick blastoderms (Hook and Sanders 1977) and in neurulating ectoderm of rats (Currie et al 1984). Our results also showed that the amount of fluorescence, indicating sites on the surface of the contact region of the neural ridge, was slightly more than that on neural grooves, but was weaker than on surface ectoderm (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It has been shown that Con A-binding sites change quantitatively during development in the ectoderm of amphibian neurulae (O'Dell etal. 1974), in chick blastoderms (Hook and Sanders 1977) and in neurulating ectoderm of rats (Currie et al 1984). Our results also showed that the amount of fluorescence, indicating sites on the surface of the contact region of the neural ridge, was slightly more than that on neural grooves, but was weaker than on surface ectoderm (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…1989). Few studies have used lectin on the developing ectoderm in vivo (Hook and Sanders 1977;Sanders and Anderson 1979;Currie etal. 1984;Slack 1985;Takahashi and Howes 1986;Takahashi 1988;Bergmann etal.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations on a variety of embryonic systems have clearly shown that developmentally regulated cell surface changes may be reflected by alterations in lectin-binding characteristics (Currie et al, 1984;Laitinen et al, 1987;Holthofer and Virtanen, 1987;Takahashi, 1988). Ultrastructural work with the early chick embryo (Hook and Sanders, 1977;Sanders and Anderson, 19791, using Con A from the glucose/ mannose group and WGA from the glucosamine group, has previously indicated that cell surface oligosaccharide changes can be detected during the process of gastrulation. Subsequently, more detailed information on such stages has been forthcoming from monoclonal antibody-binding studies (Thorpe et al, 1988;Loveless et al, 19901, and this, together with the availability of a wide panel of biotinylated lectins, has made possible correlative studies with these two approaches (Muramatsu, 1988a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Con A and WGA have been ultrastructurally localized during gastrulation previously ( Hook and Sanders, 1977;Sanders and Anderson, 1979). In the case of RCA the binding was highly localized.…”
Section: Electron Microscopymentioning
confidence: 95%
See 1 more Smart Citation